Analisis Cost Recovery dan Pengaruhnya terhadap Penerimaan Negara dari Sektor Minyak dan Gas Bumi - , Nilasari Febriarti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Extractive natural resources, which are oil and gas, always seems interesting to be discussed. Their portion to government revenue, whether from profit sharing or taxes, put big part on it. This thesis is meant to describe how the profit sharing of oil and gas in Indonesia. By knowing the profit sharing flow, we can figure out the elements of fiscal terms that build the profit sharing flow. Cost recovery is one of the key element in profit sharing. The amount can affect the government revenue. Therefore, governmentâs policy on cost recovery plays important role to control it. The policy should be not dis-incentive for oil and gas contractor.